Z′ Resonance and Associated Zh Production at Future Higgs Boson Factory: ILC and CLIC - A. Gutiérrez-Rodríguez; M. A. Hernández-Ruíz (Advances in High Energy Physics)
We study the prospects of the B-L model with an additional Z′ boson to be a Higgs boson factory at high-energy and high-luminosity linear electron positron colliders, such as the ILC and CLIC, through the Higgs-strahlung process e+e-→(Z,Z′)→Zh, including both the resonant and the nonresonant effects. We evaluate the total cross section of Zh and we calculate the total number of events for integrated luminosities of 500–2000 fb−1 and center of mass energies between 500 and 3000 GeV. We find that the total number of expected Zh events can reach 106, which is a very optimistic scenario and it would be possible to perform precision measurements for both Z′ and Higgs boson in future high-energy e+e- colliders experiments.